Three-dimensional numerical simulations of oblique internal solitary wave-wave interactions in the South China Sea - Jia, Yuxia; Gong, Yankun; Zhang, Zheen; Yuan, Chunxin; Zheng, Peng (Frontiers in Marine Science, 2024)
Satellite images show that the oblique internal solitary wave-wave interactions frequently occur in the South China Sea, especially in the periphery of Dongsha Island. Depending on the amplitudes and angles of initial oblique waves, theoretical works illustrated that the evolution pattern falls into different regimes characterised by the respective four-fold augmentation of wave amplitudes (relative to the initial waves) and occurrence of Mach stem waves in the interaction region. Nevertheless, these results were based on the reduced theories rooted from the primitive Navier-Stokes equations and the disparities induced by these simplifications with the scenarios in realistic ocean are still unclear. To fill this research gap, three-dimensional numerical simulations in the South China Sea are used to evaluate the oblique internal solitary wave-wave interactions.It is found that transformations between mode-1 and mode-2 waves occur near the Dongsha Island when two waves obliquely collide, together with a small portion of energy is converted into higher modes, most of which is dissipated locally due to their unstable vertical structures. This conclusion has been seldom reported in previous studies (if any). These oblique interactions are essentially nonlinear and impacted by the dynamical factors, such as varying depth, background current, etc., exhibiting complicated variations of waveforms and energy, which, further, enhance the mixing at local sites in the mechanism of both shear and convective instabilities indicated by the Richardson number.